Impact of culture systems on growth and plumbagin yield of in vitro Drosera binata Labill. - Promchiangsa, Teerawech; Kongbangkerd, Anupan; Muansup, Teerapat; Kunakhonnuruk, Boworn (Agriculture and Natural Resources, 2026)
Importance of the work: Guidelines are required for the conservation of the carnivorous plant Drosera binata Labill. in the wild, to ensure sufficient supply for pharmaceutical use. Objectives: To compare the effects of different cultivation systems on the in vitro growth, development and plumbagin production of D. binata. Materials and Methods: Young shoots of D. binata were cultured using three different cultivation systems: semi-solid (SSS), continuous immersion (CIS) and temporary immersion (TIS). Half-strength Murashige and Skoog medium was utilized in all three culture systems. The growth and plumbagin production were examined at the 8th week of culture. Results: CIS promoted superior growth and development compared to SSS and TIS, as evidenced by higher fresh and dry weights per clump and an increased shoot number. However, the leaf length was greatest using TIS. Considering growth performance per replication at the 8th week of culture, explants cultured in CIS had significantly higher numbers of shoots, as well as greater fresh and dry weights, than those cultured in SSS or TIS. In addition, the maximal biomass using CIS was more than twice that from TIS or SSS. The highest plumbagin production was obtained from TIS, followed by CIS and SSS. Main finding: The findings should serve as a useful foundation for the tissue culture of Drosera species, ensuring sufficient supply for future conservation in nature and the production of pharmaceutical compounds.